2023
DOI: 10.2196/preprints.40819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender Parity Analysis of the Editorial Boards of Influential Dermatology Journals: Cross-Sectional Study (Preprint)

Abstract: UNSTRUCTURED This study underscores the persistent underrepresentation of women in academic dermatology leadership positions by examining the gender composition of editorial boards across top dermatology journals, emphasizing the urgent need for proactive strategies to promote diversity, equity, and inclusion.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…One review study of all dermatology journals found that only 22% of editorial board members were women [ 8 ]. Another recent analysis exploring gender parity of the top 20 dermatology journals’ editorial boards found that women comprised a median of 33.4% (IQR 27.2%-46.9%) of their editorial boards [ 9 ]. Only in 4 of the 20 top journals did women comprise a >50% average of the editorial board [ 9 ], even though a 2018 report by the Association of American Medical Colleges found that 51% of full-time, faculty dermatologists are women [ 10 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…One review study of all dermatology journals found that only 22% of editorial board members were women [ 8 ]. Another recent analysis exploring gender parity of the top 20 dermatology journals’ editorial boards found that women comprised a median of 33.4% (IQR 27.2%-46.9%) of their editorial boards [ 9 ]. Only in 4 of the 20 top journals did women comprise a >50% average of the editorial board [ 9 ], even though a 2018 report by the Association of American Medical Colleges found that 51% of full-time, faculty dermatologists are women [ 10 ].…”
mentioning
confidence: 99%
“…Another recent analysis exploring gender parity of the top 20 dermatology journals’ editorial boards found that women comprised a median of 33.4% (IQR 27.2%-46.9%) of their editorial boards [ 9 ]. Only in 4 of the 20 top journals did women comprise a >50% average of the editorial board [ 9 ], even though a 2018 report by the Association of American Medical Colleges found that 51% of full-time, faculty dermatologists are women [ 10 ]. Among the top 20 journals, 75% had a male editor-in-chief [ 9 ] and 81% of all dermatology journals had a male editor-in-chief [ 8 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation